2023
DOI: 10.5005/jp-journals-10005-2448
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Traumatic Injuries to Permanent Anterior Teeth and Predisposing Risk Factors among Government and Private School Children of Kakinada and Rajanagaram of East Godavari District

Abstract: A bstract Aim To determine the prevalence of traumatic dental injuries (TDI) in permanent anterior teeth and their association with risk factors among children aged 7–13 years of government and private schools in Kakinada and Rajanagaram of East Godavari district, Andhra Pradesh, India. Materials and methods A cross-sectional study was carried out among 2,325 school children aged 7–13 years. Each child was examined for TDI, degree of overjet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Early interceptive orthodontic care has proven effective as a preventive measure. In addition, mouth guards and face shields can affect the frequency and intensity of traumatic dental injury (TDI) during physical activity 5 Tooth trauma is unpredictable when it occurs so it is difficult to establish precise preventive measures and prognosis of inj ury. Certain injuries require frequent visits and/or inspections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early interceptive orthodontic care has proven effective as a preventive measure. In addition, mouth guards and face shields can affect the frequency and intensity of traumatic dental injury (TDI) during physical activity 5 Tooth trauma is unpredictable when it occurs so it is difficult to establish precise preventive measures and prognosis of inj ury. Certain injuries require frequent visits and/or inspections.…”
Section: Discussionmentioning
confidence: 99%
“…Houses are the most frequently occurring places, and the most common cause is unknown. The enamel fracture is the most common and the most frequently affected is the central incisive of the maxilla, but only 4.1% of the trauma subjects seek treatment 5 . While a literature study by Lam R 6 found that the prevalence of primary and permanent Traumatic Dental Injury (TDI) is highest in Sweden, which is 37%.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior teeth are more prone to fracture due to trauma and primarily affect children and adolescents. Most dental injuries involve a single tooth, the maxillary central incisors being the most frequently affected teeth with a reported prevalence of 8.1% [ 1 ]. A vertical crown-root fracture (VRF) is a longitudinal (axial) fracture involving the enamel, dentin, and cementum and extends below the gingival margin [ 2 ].…”
Section: Introductionmentioning
confidence: 99%